The Effect of Male Incarceration on Rape Myth Acceptance: Application of Propensity Score Matching Technique. Issue 6 (2nd June 2016) - Debowska, Agata; Boduszek, Daniel; Dhingra, Katie; DeLisi, Matthew
ABSTRACT: The aim is to assess the effect of imprisonment on rape myth acceptance. The research used a sample of male prisoners incarcerated for non-sexual crimes ( n = 98) and a sample of males drawn from the general population ( n = 160). Simple linear regression did not indicate a significant effect of incarceration on rape myth acceptance. After controlling for background covariates using propensity score matching, analysis revealed a positive significant effect of incarceration on rape myth acceptance. Although further research is required, results indicate that being subject to incarceration has a significant positive effect on stereotypical thinking about rape.